2009
DOI: 10.1111/j.1553-2712.2009.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Presenting Rhythm in Sudden Deaths Temporally Proximate to Discharge of TASER Conducted Electrical Weapons

Abstract: Objectives: Sudden deaths proximate to use of conducted electrical weapons (CEWs) have been attributed to cardiac electrical stimulation. The rhythm in death caused by rapid, cardiac electrical stimulation usually is ventricular fibrillation (VF); electrical stimulation has not been reported to cause asystole or pulseless electrical activity (PEA). The authors studied the presenting rhythms in sudden deaths temporally proximate to use of TASER CEWs to estimate the likelihood that these deaths could be caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…Even if one would disagree with a given criterion, it would not change (with a single exception) the results to positive scores. Except for Swerdlow et al, 11 no authors described a systematic methodology to select cases and to maximize objectivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if one would disagree with a given criterion, it would not change (with a single exception) the results to positive scores. Except for Swerdlow et al, 11 no authors described a systematic methodology to select cases and to maximize objectivity.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13] We obtained autopsy reports, emergency medical services run sheets, law-enforcement records, medical records, and deposition transcripts. We then used objective electronic records such as the ECD download (with clock drift correction), radio logs, 9-1-1 dispatch records, and audio and video recordings to build detailed timelines of each incident.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…of the 200 deaths analyzed by Swerdlow et al, 36 56 subjects collapsed within 15 minutes of the ECD shock and had the presenting rhythm reported. Four had VF and 52 had bradycardia/ asystole or pulseless electric activity.…”
Section: Prior Publications Of Cases Consistent With Taser-induced Camentioning
confidence: 99%
“…Even so, given the claim by Amnesty International 6 of 544 deaths associated with ECD use between 2001 and 2013, it is surprising that these studies did not capture at least some of these deaths, which brings their validity into question. Swerdlow et al, 36 using an Internet-based search, found 200 cases of ECD-associated, nontraumatic sudden deaths from 2001 to 2008. Thus, more deaths occurred after ECD deployment than captured by the epidemiological studies.…”
Section: Clinical Epidemiologymentioning
confidence: 99%